2018
DOI: 10.12968/ijpn.2018.24.7.316
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of trends in the pictures drawn by primary school learners in South Africa

Abstract: The presence of two or more EIs, small pictures or pictures in dark colours may indicate clinical depression. Health professionals are advised not to try to interpret the picture, but to use the picture to enhance communication. Let the child explain the picture, rather than relying only on the assessment tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Conversely, some children and families found that meaningful relationships with health care providers lent to helpful experiences as recorded in their drawings ( Woodgate et al, 2014 ). Generally, it appeared that improving communication to support enhanced understanding for children and their families was essential ( Hyslop et al, 2018 ) and, importantly, arts-based activities and interventions effectively supported this endeavor ( Abdulah & Abdulla, 2018 ; Akard et al, 2015 ; Ångström-Brännström et al, 2013 ; Ångström-Brännström & Norberg, 2014 ; Brits, 2018 ; Ebrahimpour et al, 2021 ; Galvez et al, 2021 ; Linder et al, 2018 ; Manning et al, 2017 ; Massimo & Zarri, 2006 ; Packman et al, 2008 ; Rollins, 2005 ; Soanes et al, 2009 ; Sposito et al, 2016 ; Woodgate et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, some children and families found that meaningful relationships with health care providers lent to helpful experiences as recorded in their drawings ( Woodgate et al, 2014 ). Generally, it appeared that improving communication to support enhanced understanding for children and their families was essential ( Hyslop et al, 2018 ) and, importantly, arts-based activities and interventions effectively supported this endeavor ( Abdulah & Abdulla, 2018 ; Akard et al, 2015 ; Ångström-Brännström et al, 2013 ; Ångström-Brännström & Norberg, 2014 ; Brits, 2018 ; Ebrahimpour et al, 2021 ; Galvez et al, 2021 ; Linder et al, 2018 ; Manning et al, 2017 ; Massimo & Zarri, 2006 ; Packman et al, 2008 ; Rollins, 2005 ; Soanes et al, 2009 ; Sposito et al, 2016 ; Woodgate et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…This young patient used drawings of a dragon as a metaphor for their diagnosis, often using them to explain their experiences to the nurse and family members ( Ångström-Brännström et al, 2013 ). Similarly, Brits (2018) sought to evaluate whether the HFD tool ( Koppitz, 1968 ) could be used to evaluate emotional well-being of African school-aged children in palliative care. The author found that drawing improved communication of the needs of African school-aged children in palliative care to their providers and families which is significant because communication is deemed to be the cornerstone of palliative care ( Brits, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations